Modified clock mapping biopsy sec. Della Corte-Bifulco in the preoperative assessment of excisional surgery for vulvar Paget's disease - Luigi Della Corte; Mario Ascione; Giuseppe Bifulco (Frontiers Media S.A., 2024)
We have developed a biopsy technique aimed at preoperative evaluating the extent of Paget's vulvar disease in order to plan subsequent radical vulvar surgery. The aim is to find all possible lesion sites that are not visible macroscopically, to obtain a clear evaluation of the disease spread and to tailor the radical surgical procedure to remove even microscopic lesions, avoiding recurrences and excessively destructive surgery, adopting as conservative an approach as possible. We used this procedure for the first time to establish the radicality of the surgical intervention in a 68-year-old patient initially suffering from a single invasive vulvar Paget's lesion.